Clinical and echocardiographic outcomes of patients with mitral annular calcification undergoing mitral valve surgery: a 10-year single center experience - Kanade, Rahul; Gosden, Jack; Roland, Jonathan; Aly, Mohamed; Reisinger, Maximilian; Kachel, Mateusz; Pirelli, Luigi; Takeda, Koji; Argenziano, Michael; Takayama, Hiroo; Geirsson, Arnar; Wang, Chunhui; et al. (Annals of Cardiothoracic Surgery; Vol 14, No 6 (November 30, 2025): Mitral Annular Calcification, 2025)
Background: Mitral annular calcification (MAC) is a chronic and degenerative process, affecting the mitral valve annulus. MAC complicates the decision over the appropriate surgical approach to mitral valve disease. Distorted valvular anatomy increases surgical risk and therefore requires careful patient selection. Here, we report our single-center experience performing mitral valve surgery in the setting of MAC over a 10-year period. Methods: This is a 10-year retrospective analysis of 172 patients with MAC. Sixty-seven patients underwent MAC severity scoring using a 10-point system based on computed tomography (CT). The primary outcome was 30-day mortality, readmission, reoperation, stroke, prolonged ventilation, renal failure and deep sternal infection. Secondary analyses stratified MAC by underlying mitral disease type as well as evaluated outcomes by CT severity score. Patients without MAC undergoing mitral valve replacement surgery during the same time period served as controls. Results: The 30-day mortality was significantly higher in MAC patients compared with non-MAC (9.9% vs. 4.2%, P